First- and Second-trimester Down Syndrome Screening: Current Strategies and Clinical Guidelines - Sheng-Wen Shaw; Jenn-Jeih Hsu; Chien-Nan Lee; Ching-Hua Hsiao; Chih-Ping Chen; T'sang-T'ang Hsieh; Po-Jen Cheng (Elsevier, 2008)
Down syndrome (DS) is the most common human disease caused by a structural chromosome defect. The original screening test for DS was maternal age or a history of a previously affected infant. Maternal serum screening has been incorporated into routine prenatal checkup in Taiwan since 1994. We used free β-human chorionic gonadotropin and α-fetoprotein (double test) as the serum markers, and this was carried out between the 15 to 20th week of gestation. The overall detection rate was 56% and was compatible with studies of Caucasian populations. The impact of double tests in Taiwan has shown itself by a dramatic lowering of the rate of DS live birth from 0.63 before screening to 0.16 per 1,000 live births at present. However, because of its relatively low detection rate and poor cost-effectiveness, the double test is not justified as a routine screening tool currently. First-trimester combined test is now becoming more widely available and provides increased sensitivity when detecting DS; it has a detection rate of approximately 85% with a false-positive rate of 5%. Nuchal translucency measurement requires ongoing quality control and sufficient certificated obstetricians; therefore, first-trimester ultrasound is limited only in designated centers. The quadruple test, having comparable detection rate, should be considered for incorporation into second-trimester screening in Taiwan in the near future. Other screening approaches and combinations have also been utilized in the Western countries. In this review, we outline the various options with respect to DS screening and hope that this will provide practical information for physicians offering such screenings. [Taiwan J Obstet Cynecol 2008;47(2):157-1 62]